2017
DOI: 10.1093/schbul/sbx077
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Mitochondria Transfer Improves Neuronal Differentiation of Schizophrenia-Derived Induced Pluripotent Stem Cells and Rescues Deficits in a Rat Model of the Disorder

Abstract: Dysfunction of mitochondria, key players in various essential cell processes, has been repeatedly reported in schizophrenia (SZ). Recently, several studies have reported functional recovery and cellular viability following mitochondrial transplantation, mostly in ischemia experimental models. Here, we aimed to demonstrate beneficial effects of isolated active normal mitochondria (IAN-MIT) transfer in vitro and in vivo, using SZ-derived induced pluripotent stem cells (iPSCs) differentiating into glutamatergic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 61 publications
1
69
1
6
Order By: Relevance
“…[ 108,109 ] In addition to the genetic models of mitochondria abnormalities, the maternal immune activation (MIA) model of SCZ presents a significant mitochondrial dysfunction [ 110 ] that leads to multiple SCZ‐relevant neurobehavioral deficits, [ 111,112 ] which were restored by the intra‐PFC injection of isolated normal mitochondria. [ 113 ] The above studies suggest that mitochondrial dysfunction plays a causal role in generating SCZ‐like neurobehavioral deficits.…”
Section: Mitochondria For the Normal Neurobiological Function Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…[ 108,109 ] In addition to the genetic models of mitochondria abnormalities, the maternal immune activation (MIA) model of SCZ presents a significant mitochondrial dysfunction [ 110 ] that leads to multiple SCZ‐relevant neurobehavioral deficits, [ 111,112 ] which were restored by the intra‐PFC injection of isolated normal mitochondria. [ 113 ] The above studies suggest that mitochondrial dysfunction plays a causal role in generating SCZ‐like neurobehavioral deficits.…”
Section: Mitochondria For the Normal Neurobiological Function Of Thementioning
confidence: 99%
“…Furthermore, not only do chemicals that boost mitochondrial function result in recovery in SCZ‐like behavioral deficits, but the transfer of isolated active normal mitochondria into the brains of MIA model rats also resulted in neurobehavioral recovery, accompanied by the functional restoration of mitochondria. [ 113 ] The fact that disturbance of mitochondrial function results in SCZ‐relevant neurobehavioral abnormalities, and that one can rescue SCZ‐like behavioral deficits by restoring mitochondrial function further suggests the causal role of mitochondrial dysfunction in various SCZ‐relevant neurobehavioral abnormalities. All these animal studies point to the fact that chemicals that enhance mitochondrial function can serve as a valid therapeutic target for mitochondria‐related deficits in SCZ ( Table 5 ).…”
Section: Mitochondrial Function As a Potential Therapeutic Target Formentioning
confidence: 99%
“…A mitochondria transfer to patient’s cells with SZ showed the cells receiving mitochondria transfer from controls had a higher mitochondria membrane potential compared to the same cells that did not receive a mitochondria transfer [77]. Mitochondria membrane potential is maintained at sufficiently high levels to promote ADP to ATP conversion.…”
Section: Interaction Analysis Of Mitochondrial and Nuclear-encoded Genesmentioning
confidence: 99%
“…To assess the cause-effect relationship for mitochondrial dysfunction in SCZ, Robicek et al [ 84 ] most recently investigated mitochondria transfer to SCZ-iPSC derived neurons [ 78 ]. Several studies have shown that mitochondria can transfer between cells via various contact modes, comprising cell fusion, junction, and tunneling nanotube formation [ 103 ].…”
Section: Introductionmentioning
confidence: 99%